1994
DOI: 10.1002/mpo.2950220605
|View full text |Cite
|
Sign up to set email alerts
|

Radiation therapy for alveolar soft‐part sarcoma

Abstract: A clinical experience with radiotherapy in 18 patients with alveolar soft-part sarcoma is presented. Adjuvant radiotherapy was associated with prolonged local control in six of six patients without metastatic disease at diagnosis; later one patient relapsed systematically. Meaningful palliation was achieved in all patients with extra-skeletal (and possibly skeletal) metastatic disease. Radiation therapy may be beneficial for patients with alveolar soft-part sarcoma by enhancing local control achieved with limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
3

Year Published

1996
1996
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 19 publications
1
24
0
3
Order By: Relevance
“…Recently, Sherman et al [14] documented excellent local control in six adult patients with this neoplasm who received adjuvant or preoperative radiotherapy and thus recommended that all adult patients with localized disease receive radiation therapy. We cannot recommend the routine use of radiotherapy in children with completely resected tumors in which the margin of resection is adequate; local control was not a problem in our patients, and the long-term side effects of radiotherapy in the growing child (limb length discrepancies, second malignant neoplasms) may outweigh its benefits.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, Sherman et al [14] documented excellent local control in six adult patients with this neoplasm who received adjuvant or preoperative radiotherapy and thus recommended that all adult patients with localized disease receive radiation therapy. We cannot recommend the routine use of radiotherapy in children with completely resected tumors in which the margin of resection is adequate; local control was not a problem in our patients, and the long-term side effects of radiotherapy in the growing child (limb length discrepancies, second malignant neoplasms) may outweigh its benefits.…”
Section: Discussionmentioning
confidence: 98%
“…Although the tumors are slow growing locally, they metastasize early and metastatic lesions may bring the patient to clinical attention before the primary lesion is discovered. Whereas some authors have found radiation therapy useful for local control of lesions if the patient does not have systemic metastasis, 16 other authors have found no significant longterm prognostic benefit to radiation and chemotherapy. 7,17,18 Complete surgical resection of an isolated primary lesion appears to give the best chance for disease-free survival, but because many cases are metastatic at the time of presentation, metastatectomy is also a palliative option.…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy was somewhat effective, especially as adjuvant therapy for local control in patients with inadequate surgical margins [20,25]; however, the role of radiotherapy in ASPS has not been clearly defined [20].…”
Section: Discussionmentioning
confidence: 99%